Penanganan Pasien Hipertermia Menggunakan Terapi Tepid Sponge: Laporan Kasus - mei lestari; Ahmadi; Vinnika Kamaisya R (Universitas Nazhatut Thullab Al- Muafa Sampang, 2023)
Introduction: Hyperthermia is a condition where the body temperature has increased more than 37.5oC. The normal value of body temperature is 36.5°C –37oC. Peripheral sponge therapy can be used in hyperthermic patients. Objectives: The purpose of this study is to describe nursing care with the application of tepid sponge therapy to reduce hyperthermia. Methods: The writing used a descriptive method with a nursing process approach consisting of assessment, diagnosis, planning, implementation and evaluation. Research subjects 2 clients with hyperthermia nursing problems. Results: The results showed that on the 3rd day, An